Development of Interactive Mathematics Multimedia Teaching Materials for Building Space in Class V Primary Schools - Gartika, Euis; Rahayu, Wardani; Utomo, Erry (International Journal for Educational and Vocational Studies, 2019)
This study aims to produce the development of interactive multimedia that is feasible to use in the mathematics of building space. The subjects of this study were in class V of Panaragan 1 Elementary School in Bogor, Semplak 2 Elementary School, and Bogor 1 Police Public Elementary School. This interactive multimedia development uses a type of research and development concerning the model developed by Lee and Owens, there are 5 stages: assessment / analyze, instructional design, development, implementation, and evaluation. The media developed was validated by material and media experts before being tested on students. The instruments used to collect the data were 4.4 expert media feasibility test questionnaires, material expert questionnaire feasibility test 4.3 trial language feasibility expert 4.2, declared feasible for use in learning.